2015
DOI: 10.4103/1319-2442.157362
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of acute kidney injury among the critically ill neonates

Abstract: Acute kidney injury (AKI) is a complex disorder with clinical manifestations ranging from mild dysfunction to complete kidney failure. The published literature on the incidence and outcome of AKI in the critically ill neonatal population is scarce. The aim of this study was to evaluate the types, the associated risk factors and short-term outcome of AKI in the critically ill neonates. A cohort study was conducted including 100 critically ill neonates successively admitted to the Neonatal Intensive Care Unit. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…These results are consistent with a study published by Shalaby et al [ 13 ], which concurred that the overall mortality rate was 28.3% and that neonatal AKI was significantly associated with mortality but not with the length of hospital stay. A similar finding has been noted by Criss et al [ 18 ], who reported that mortality rates among neonates with AKI were 35.9%. They further surmised that neonates with AKI had higher mortality and a greater chance of death, but the effect of LOS on survivors did not reach statistical significance, which agreed with our results.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with a study published by Shalaby et al [ 13 ], which concurred that the overall mortality rate was 28.3% and that neonatal AKI was significantly associated with mortality but not with the length of hospital stay. A similar finding has been noted by Criss et al [ 18 ], who reported that mortality rates among neonates with AKI were 35.9%. They further surmised that neonates with AKI had higher mortality and a greater chance of death, but the effect of LOS on survivors did not reach statistical significance, which agreed with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Nowadays, the diagnosis of neonatal AKI has not been unified. There are five definitions that describe the state of neonatal AKI in our meta-analysis: (1) arbitrary definition mainly based on absolute serum creatinine (SCr) ≥1.5 mg/dl;( 4 , 23 , 24 , 27 ), (2) arbitrary definition based on absolute SCr >1 mg/dl and >1.3 mg/dl (for ≥33 weeks and <33 weeks, respectively) after 48 h of life;( 12 , 22 ), (3) AKIN definition based on absolute SCr ≥ 0.3mg/dl or SCr ≥1.5 times baseline within 48 h or urine volume <0.5 ml/kg/h for 6 h;( 11 , 21 , 25 ), (4) KDIGO definition based on absolute SCr ≥0.3 mg/dl within 48 h or SCr ≥1.5 times baseline, which is known or presumed within 7 days, or urine volume <0.5 ml/kg/h for 6 h;( 1 , 6 , 29 ), and (5) modified KDIGO definition changes the baseline to previous trough value in SCr ( 2 , 5 , 20 , 26 , 28 , 30 , 31 , 45 ). As we can see, the arbitrary definitions are mainly dependent on an absolute increase in SCr for at least 1 mg/dl, whose critical value is higher than that of AKIN and KDIGO.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory failure and peritonitis have been reported as risk factors for poor prognosis in previous studies 10 26 28 . Kidney failure, one of the most severe complications of NEC 30 , was first identified as a risk factor for NEC mortality in a pilot study (n = 19) conducted by Rivera-Moreno in 1999 31 . The findings of the present study further demonstrated the association between kidney failure and mortality, and further studies should be conducted to clarify the molecular mechanism underlying this association.…”
Section: Discussionmentioning
confidence: 99%